2022
DOI: 10.3390/jmse10070907
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Variation of Tidal Mixing Asymmetry and Its Impact on the Longitudinal Sediment Transport in Turbidity Maximum Zone of Salt Wedge Estuary

Abstract: The lateral bathymetry in the estuary results in different degrees of tidal mixing asymmetry, which has significant impacts on the longitudinal sediment transport by changing the temporal variation of vertical eddy diffusion. This study focus on the lateral variation of tidal mixing asymmetry and longitudinal sediment transport at the landward boundary of turbidity maximum zone in the North Channel of Yangtze estuary, which is a typical time-dependent salt wedge estuary. A transect survey was carried out in De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…These increase and decrease in tidal asymmetry also affect the residual flows (Wang, Jeuken, and De Vriend, 1999). The increased vertical salinity gradient near the bridge can enhance the tidal asymmetry (Teng et al, 2022). In Gyeonggi Bay, the horizontal gradient of water temperature is low at less than 5 degrees, whereas the gradient of salinity is high at more than 20 psu.…”
Section: Discussionmentioning
confidence: 99%
“…These increase and decrease in tidal asymmetry also affect the residual flows (Wang, Jeuken, and De Vriend, 1999). The increased vertical salinity gradient near the bridge can enhance the tidal asymmetry (Teng et al, 2022). In Gyeonggi Bay, the horizontal gradient of water temperature is low at less than 5 degrees, whereas the gradient of salinity is high at more than 20 psu.…”
Section: Discussionmentioning
confidence: 99%
“…For all behaviors of the suspended sediments over the entire period, the horizontal fluxes for those uplifted above the position of suspended sediments assumed to be free of fluctuations by coastal seiches reached 51×10 −3 kg m −1 s −1 (standard SSC: 20 mg l −1 ) at M1 and 83×10 −3 kg m −1 s −1 (standard SSC: 20 mg l −1 ) at M2 (Figure 10). Although the sediment diffusion was suppressed by enhanced s 2 in the neap tides (N I and N II ) (Teng et al, 2022; Zhang…”
Section: Uplift Of Suspended Sediments By Coastal Seichesmentioning
confidence: 99%
“…Regardless of the year and season, the low slack water seems to be the most important tidal period because there are always large surface-suspended sediment concentrations and variations at that particular period. The SSSC recorded during low slack water could be the remaining SSSC from ebb resulting from the resuspension of the bottom deposited sediment by the stronger currents [52,59]. It can be observed that throughout the tidal periods, high SSSC location is slightly shifted in the upstream direction during ebb at stations C, D, and E in spring tides and in stations B and D during neap tides before coming back to its normal area D, E, and F at the other tidal phases, especially in spring tides (Figure 10b).…”
Section: Tidal Inputs On Sssc and Spsmentioning
confidence: 99%